2009
DOI: 10.1136/jmg.2008.063701
|View full text |Cite
|
Sign up to set email alerts
|

A pilot open label, single dose trial of fenobam in adults with fragile X syndrome

Abstract: Objective:A pilot open label, single dose trial of fenobam, an mGluR5 antagonist, was conducted to provide an initial evaluation of safety and pharmacokinetics in adult males and females with fragile X syndrome (FXS). Methods: Twelve subjects, recruited from two fragile X clinics, received a single oral dose of 50-150 mg of fenobam. Blood for pharmacokinetic testing, vital signs and side effect screening was obtained at baseline and numerous time points for 6 h after dosing. Outcome measures included prepulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
239
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(250 citation statements)
references
References 27 publications
8
239
0
3
Order By: Relevance
“…In an open label, single-dose trial of fenobam in 12 adults with FXS (6 males and 6 females), half of the subjects showed at least 20% improvement in prepulse inhibition (PPI) -a measure of sensory gating -within 1 hour of dosing, and most subjects showed clinical improvement in areas of hyperactivity and anxiety (21). It was also well tolerated in these participants and no serious adverse events were reported.…”
Section: Metabotropic Glutamate Receptor 5 (Mglur) Antagonistsmentioning
confidence: 99%
“…In an open label, single-dose trial of fenobam in 12 adults with FXS (6 males and 6 females), half of the subjects showed at least 20% improvement in prepulse inhibition (PPI) -a measure of sensory gating -within 1 hour of dosing, and most subjects showed clinical improvement in areas of hyperactivity and anxiety (21). It was also well tolerated in these participants and no serious adverse events were reported.…”
Section: Metabotropic Glutamate Receptor 5 (Mglur) Antagonistsmentioning
confidence: 99%
“…Fenobam single-dose was found to be safe in a small pilot trial of adults with FXS. The trial showed improvements in hyperactivity and anxiety, and in prepulse inhibition [86]. As noted earlier, this work is important to delineate neurobiological phenotypes within FXS but can be only demonstrated through double-blind, randomized, placebo-controlled studies.…”
Section: Targeted Treatments In Fragile X Syndromementioning
confidence: 99%
“…6 This mimics excessive group 1 metabotropic glutamate receptor signaling, which is an insight that has initiated several FXS clinical trials with therapeutic approaches directly targeting this pathway. [7][8][9] FXS is almost exclusively diagnosed by molecular testing for CGGrepeat expansion, even though the causal link to FXS is not directly because of repeat expansion but rather because of the loss of the encoded FMR protein. This CGG-repeat test is among the most frequently ordered genetic tests and is standard of care for any child not meeting developmental milestones.…”
Section: Introductionmentioning
confidence: 99%